Feasibility Meets Implementation Science: Narrowing the Research-To-Practice Gap for Exercise Activity in Multiple Sclerosis - Smith, James; van der Groen, Onno; Learmonth, Yvonne (2023)
Background: There is a need to identify why multiple sclerosis exercise research is not translating into real-world participation. To lay the foundations of strong clinical research, considering the translational element of implementation science at the feasibility phase of a trial is vital. Methods: Document analysis was used to examine document sources on exercise activity interventions designed for people living with multiple sclerosis. Document sources focused on multiple sclerosis research that incorporated exercise pre scription elements and behaviour change and were feasibility studies incorporating aspects of implementation science. Results: Implementation science should come much earlier than the efficacy or effectiveness research pipeline. An alternate view is outlined where feasibility and implementation science should meet based on case examples that have not yet shown strong efficacy or effectiveness. Findings from our key themes indicate a need for a cyclical iterative approach to the translational process. Multiple aspects of feasibility and how it can be assessed using an implementation science lens to support more successful interventions are provided. The determination of feasibility in behaviour change should involve implementation science as feasibility is drawn on for theory development, optimising the intervention design and quality of implementation strategies, and identifying those delivering the intervention before conducting efficacy and effectiveness research. Conclusions: Document analysis methodology is underused in qualitative research and was appropriate to use as it was a very resource, time-efficient and an unobtrusive process that could track change and development to explore the integration of implementation science at the feasibility phase, with the findings indicating the earlier implementation science is introduced into multiple sclerosis exercise interventions the better.